2017
DOI: 10.1021/acs.jpcc.7b10262
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Evaluation of Dopant Energetics and the Modulation of Ultrafast Carrier Dynamics in Cu-Doped CdSe Nanocrystals

Abstract: Cyclic voltammetric and femtosecond transient absorption (TA) measurements on Cu+-doped CdSe nanocrystals (NCs) were utilized to reveal the energetics of the electroactive Cu+ dopant with respect to the band energies of CdSe NC host and the influence of Cu in tuning the carrier dynamics, respectively. Oxidation–reduction peaks due to an electroactive dopant within CdSe NC host have been traced to determine its energy level which was correlated to the dopant emission energy and Stokes shift. The low doping dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Although not reported in refs. 35,36 , we suspect the QDs used there might have a much slower hole capturing rate, thus allowing hot electron relaxation via energy transfer to the hole. This is likely due to the low Cu concentration in the QDs used there, because the hole transfer rate should roughly scale with the number of available Cu dopants inside the QD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not reported in refs. 35,36 , we suspect the QDs used there might have a much slower hole capturing rate, thus allowing hot electron relaxation via energy transfer to the hole. This is likely due to the low Cu concentration in the QDs used there, because the hole transfer rate should roughly scale with the number of available Cu dopants inside the QD.…”
Section: Resultsmentioning
confidence: 99%
“…Gamelin et al studied carrier recombination dynamics in n -type Cu-doped CdSe/CdS QDs and found an ultrafast (~260 ps), Auger-dominated negative trion recombination pathway involving two band edge electrons and a Cu-captured hole 34 , but no hot carrier relaxation dynamics was reported in this work. Slightly longer-lived hot electrons in Cu:CdSe QDs as compared to CdSe QDs (700 fs vs. 400 fs) were reported in the works by Ghosh et al 35 and by Patra et al 36 , but such a marginal improvement in hot electron lifetime is not sufficiently impactful for hot electron devices. Thus, in order to realize long-lived hot electrons in Cu:QDs, it is essential to optimize the hole capturing process by Cu dopants and to directly measure the rate of this process and compare it with hot electron relaxation rate.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3] While environmental concerns have spurred research interest in heavymetal-free multinary and transition metal doped structures, their optical transitions are not well understood, and significantly differ from Cd and Pb chalcogenides. [4][5][6][7][8][9][10][11][12][13] For example, QDs with Cu, or Mn cations have large Stokes shifts (∆ " , defined as the energy difference between absorption and emission energies), broad ensemble spectral linewidths, long radiative lifetimes, and tunable magnetic exchange interactions. 6,14 One possible reason for these peculiar properties is the smaller ionic radii of 3d transition metals, which have greater polarizing power than Cd or Pb, and should form more covalent bonds with early chalcogens.…”
Section: Introductionmentioning
confidence: 99%
“…The unit of energy is eV. The values are taken from the literature . c) EQE and CE of Device A. d) Current density and luminance of Device A. e) The EL spectrum of Device A and the PL spectrum of CdSe CQWs with a 0% Cu‐doped concentration film.…”
Section: Summary Of Led Performancesmentioning
confidence: 99%
“…As shown in Figure 3a, the maximum EQE of Device B is 0.146%, which is nine times greater than that of Device A and is the highest reported value for single-nanocrystal LEDs with dual emission. [30] Previously, Chen et al achieved a twofold increase in the EQE of CQW-LEDs by exchanging the long ligands of CQWs with short ones, [15] while Giovanella et al [18,22,[40][41][42] c) EQE and CE of Device A. d) Current density and luminance of Device A. e) The EL spectrum of Device A and the PL spectrum of CdSe CQWs with a 0% Cu-doped concentration film. Compared with the PL spectrum of the film, with an emission of 516 nm and an FWHM of 10 nm, the EL spectrum of Device A is slightly redshifted (520 nm), and the EL FWHM is relatively widened (12 nm).…”
mentioning
confidence: 99%